Video Conference Application in Emergency Remote Learning: Experience, Preference, and Satisfaction - Dhimas Onny Permadi; Francisca Maria Ivone; Mirjam Anugerahwati (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The purpose of this study is to look at foreign language faculty members' and students' experiences, preferences, and satisfaction with video conference apps for emergency remote learning. This quantitative study collected data using a multiple-choice and Likert scale questionnaire. Data from the questionnaire were analysed using a single table analysis. The findings indicated that both Zoom, and Google Meet have a generally favourable opinion of video conference apps' instructional substance, efficacy, engagement, and idea-sharing. Nonetheless, Zoom was strongly favoured by most respondents due to its support for collaboration, teaching strategy, motivation, and material sharing. Despite that Google Meet had a lower rating, it can be a viable alternative for teachers to meet learning objectives, stimulate discussion, and be utilized on a variety of devices.Abstrak: Tujuan dari penelitian ini adalah untuk melihat pengalaman, preferensi, dan kepuasan pengajar bahasa asing dan mahasiswa dengan aplikasi konferensi video untuk pembelajaran jarak jauh darurat. Penelitian kuantitatif ini mengumpulkan data dengan menggunakan kuesioner pilihan ganda dan skala Likert. Temuan menunjukkan bahwa substansi instruksional aplikasi konferensi video, keberhasilan, keterlibatan, dan berbagi ide dalam aplikasi Zoom dan Google Meet secara umum mendapat respon yang baik. Meskipun demikian, Zoom sangat disukai oleh mayoritas responden karena dukungannya untuk kolaborasi, strategi mengajar, motivasi, dan berbagi materi. Terlepas dari Google Meet memiliki peringkat yang lebih rendah, applikasi ini dapat menjadi alternatif yang layak bagi guru untuk memenuhi